Boom - Crisis - Heritage King Coal and the Energy Revolutions after 1945 - Bluma, Lars; Farrenkopf, Michael; Meyer, Torsten (Veröffentlichungen aus dem Deutschen Bergbau-Museum Bochum, 2021)
Boom - Crisis - Heritage, these terms aptly outline the history of global coal mining after 1945. The essays collected in this volume explore this history with different emphases and questions. The range of topics also reflects this broad approach. The first section contains contributions on political, social and economic history. They address the European energy system in the globalised world of the 20th and 21st centuries as well as specific social policies in mining regions. The second section then focuses on the medialisation of mining and its legacies, also paying attention to the environmental history of mining. The anthology, which goes back to a conference of the same name at the Deutsches Bergbau-Museum Bochum, thus offers a multi-faceted insight into the research field of modern mining history.